Early postoperative arrhythmias after pediatric congenital heart disease surgery: a 5-year audit from a lower- to middle-income country - Sidra Ishaque; Saleem Akhtar; Asma Akbar Ladak; Russell Seth Martins; Muhammad Kamran Younis Memon; Alisha Raza Kazmi; Fatima Mahmood; Anwar ul Haque (Acute and Critical Care, 2022)
Background Arrhythmias are known complication after surgery for congenital heart disease (CHD). This study aimed to identify and discuss their immediate prevalence, diagnosis and management at a tertiary care hospital in Pakistan. Methods A retrospective study was conducted at a tertiary care hospital in Pakistan between January 2014 and December 2018. All pediatric (<18 years old) patients admitted to the intensive care unit and undergoing continuous electrocardiographic monitoring after surgery for CHD were included in this study. Data pertaining to the incidence, diagnosis, and management of postoperative arrhythmias were collected. Results Amongst 812 children who underwent surgery for CHD, 185 (22.8%) developed arrhythmias. Junctional ectopic tachycardia (JET) was the most common arrhythmia, observed in 120 patients (64.9%), followed by complete heart block (CHB) in 33 patients (17.8%). The highest incidence of early postoperative arrhythmia was seen in patients with atrioventricular septal defects (64.3%) and transposition of the great arteries (36.4%). Patients were managed according to the Pediatric Advanced Life Support guidelines. JET resolved successfully within 24 hours in 92% of patients, while 16 (48%) patients with CHB required a permanent pacemaker. Conclusions More than one in five pediatric patients suffered from early postoperative arrhythmias in our setting. Further research exploring predictive factors and the development of better management protocols of patients with CHB are essential for reducing the morbidity and mortality associated with postoperative arrhythmia.